KAJIAN AWAL MIKROSKOPI TEKSTUR MIKRO PERMUKAAN GRANULA POLIMER SEBAGAI HASIL PROSES GRANULASI - Sitorus (NIM : 20599012), Berlian
Abstract : In general, polymeric article producers receive polymeric materials in granular form, which bring their characteristic as a result of their thermomechanical treatment during granulation. However, structural and physical properties of the granules are the important factor in selecting the most suitable polymer for the producer in order to ascertain the application. Those properties could be to some extent revealed from the features on its granular textures, which might be propagated while granular polymers are further fabricated. On the other hand, microscopic technique is a simple method in analyzing surface texture which required a rapid and relatively easy specimen preparation. Therefore, we attempt to study granular structure of various polymer samples which are investigated by microscopic method in turn their correlation with interpreted surface textural information is being sought. Polymeric materials used as samples in this research were low density polyethylene (LDPE), high density polyethylene (HDPE), polystyrene and polysulfone. The aim of this experiment was to reveal the structural information as received of granular materials through microscopic method, the result of which was then sought for its correlation with the results obtain from the textural analysis. Physical properties such as Tm and Tg were determined by using Thermal Analysis, crystallinity by X-Ray Diffraction and analysis of chemical functional groupings by using the Fourier Transformed Infra-Red spectroscopy. The results of which also contribute supporting evidence upon the interpretation of the structural information of the systems under study. The characterization results indicate that there were good correlation between the interpreted textural and structural information microscopically with those revealed and supported by other standard characterization techniques employed. It was also found some extent that there is a significant difference in surface texture even between the similar polymers, as they might have already been differently treated as far as thermomechanical factor is concerned during the granulation process.